EFIKASI PESTISIDA NABATI DALAM PENGENDALIAN PENYAKIT ANTRAKNOSA PADA TANAMAN CABAI (Capsicum annum L.) - Ida Hodiyah; Elya Hartini; Amir Amilin (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2019)
ABSTRACTChili grows well both in lowland and highland, and as a high economic vegetable chili is widely grown by farmers. Nevertheless, there are still many obstacle in its management among others is pest and disease attack. Antracnose disease by Colletotrichum sp. causes yield decrease even harvest failure as it attacks the fruits. The objective was to find out kinds of biopesticides and its concentration to control antracnose disease. The experiment was conducted in Faculty of Agriculture garden from July until February 2017. A Randomized Block Design was used consisted of 9 treatments i.e. A (control), B (1% soursop extract), C (2% soursop extract), D (1% siam weed extract), E (2% siam weed extract), F (1% galangal rhizome extract), G (2% galangal rhizome extract), H (1% mixture of soursop, kirinyuh, and galangal rhizome extract), and I (2% mixture of soursop, siam weed, and galangal rhizome extract). The results that the efficacy of application of 1% to 2% extracts of soursop leaf, siam weeds, and galangal rhizome, both independently and in mixture, were in the range of ineffective and less effective categories in controlling antracnose disease on red chilli.